Occupational asthma due to latex in health care workers. Issue 12 (December 1996) - Ho, A.; Chan, H.; Tse, K. S.; Chan-Yeung, M.
Abstract : Immediate hypersensitivity reactions ranging from mild urticaria to life threatening anaphylaxis after exposure to natural rubber latex have been reported frequently in health care workers while occupational asthma due to latex exposure is less well studied. The results of specific challenge tests and immunological tests in four health care workers with work related respiratory and skin disorders induced by the use of latex gloves are described. Occupational asthma was confirmed in three subjects by specific challenge tests. All had a positive skin test reaction to the latex extract; specific IgE antibodies were detected in only one subject. The fourth subject had a negative specific inhalation and skin test reaction to the latex extract. Peak expiratory flow monitoring at work and away from work showed a pattern consistent with work related asthma. These findings confirm that latex is a cause of occupational asthma in health care workers.